PENGEMBANGAN MULTIMEDIA INTERAKTIF TERINTEGRASI PENDEKATAN CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN SIKAP DAN HASIL BELAJAR PESERTA DIDIK MADRASAH IBTIDAIYAH - Ulil Maufiroh; Eko Budi Minarno; Nurlaeli Fitriah (STKIP Pesisir Selatan, 2026)
The low science learning outcomes and environmental care attitudes of students on environmental pollution materials indicate the need for more interactive and contextual learning media innovations. This study aimed to develop interactive multimedia integrated with the Contextual Teaching and Learning (CTL) approach that is valid and effective in improving environmental care attitudes and learning outcomes of fourth-grade students at MI Negeri 02 Malang City. This research employed the Research and Development (R&D) method using the ADDIE model consisting of analysis, design, development, implementation, and evaluation stages. The research subjects consisted of 54 students divided into experimental and control classes. Data collection techniques included observation, interviews, documentation, questionnaires, and pretest-posttest tests. The validation results showed that the multimedia achieved a very valid category with media expert validation of 93%, material expert validation of 91.43%, and learning expert validation of 96%. The Wilcoxon test results showed a significance value of < 0.05, indicating an improvement in learning outcomes after using the interactive multimedia. In addition, the Mann-Whitney U test showed a significant difference between the experimental and control classes. Therefore, CTL-integrated interactive multimedia is feasible and effective for improving students’ environmental care attitudes and science learning outcomes in Islamic elementary schools.